Evaluation of Reminder App for Optimization of Bladder Filling Status During Hypo-Fractionated Irradiation for Prostate Cancer: Protocol of REFILL-PAC-HYPO Trial - Dirk Rades; Jan-Dirk Küter; Michael von Staden; Ahmed Al-Salool; Christian Ziemann; Stefan Janssen; Julia Koeck; Justus Domschikowski; Charlotte Kristiansen; Christine Vestergård Madsen; Marciana N. Duma; Tobias Bartscht; et al. (Clinics and Practice)
Background/Objectives: During radiotherapy for prostate cancer, the risk of radiation cystitis is increased if the volume of the bladder is small. According to previous studies, it is important that bladder volumes are ≥200 mL. Drinking protocols may be helpful in this context. Adherence to such protocols can be challenging, and may be improved by an app reminding patients before each session of radiotherapy to drink a certain amount of water. Our prospective phase 2 trial (REFILL-PAC-HYPO, NCT06784115) evaluates the impact of a reminder app on bladder filling in prostate cancer patients treated with hypo-fractionated radiotherapy. Methods: Twenty-seven patients need to be recruited for the REFILL-PAC-HYPO trial. Radiotherapy, preferably with volumetric-modulated arc therapy, uses hypo-fractionation with 20 × 3.0 Gy over four weeks. An app reminds patients to drink water (300 mL) 45 min before each session of hypo-fractionated irradiation. On the last day of their treatment, patients are asked about their satisfaction with the app. In the case of a dissatisfaction rate of >20%, the app requires modifications. If this rate is >40%, the app is considered not useful. Additionally, patients are asked about the impact of their participation in the trial and using the app on their general attitude towards health technology. Furthermore, the phase 2 cohort is compared to a historical control group treated with hypo-fractionated radiotherapy during recent years but not supported by an app. The REFILL-PAC-HYPO trial will contribute to identifying the potential value of a reminder app for bladder filling during hypo-fractionated radiotherapy for prostate cancer.